2012
DOI: 10.1371/journal.pone.0032786
|View full text |Cite|
|
Sign up to set email alerts
|

Spike-Interval Triggered Averaging Reveals a Quasi-Periodic Spiking Alternative for Stochastic Resonance in Catfish Electroreceptors

Abstract: Catfish detect and identify invisible prey by sensing their ultra-weak electric fields with electroreceptors. Any neuron that deals with small-amplitude input has to overcome sensitivity limitations arising from inherent threshold non-linearities in spike-generation mechanisms. Many sensory cells solve this issue with stochastic resonance, in which a moderate amount of intrinsic noise causes irregular spontaneous spiking activity with a probability that is modulated by the input signal. Here we show that catfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Sinusoidal electrical stimulation to glass catfish shortens the interspike interval (ISI) in one half period and prolongs the ISI in the other half ( Bretschneider et al, 1985 ). Bursting patterns are considered to contribute to reliable signal transmission ( Izhikevich et al, 2003 ) and are often found in electroreceptors and their associated cells ( Wilkens et al, 1997 ; Neiman and Russell, 2002 ; Oswald et al, 2004 ; Lankheet et al, 2012 ). Daphnia or Ornstein-Uhlenbeck Gaussian noise induce bursting in the electroreceptors of paddle fish ( Wilkens et al, 1997 ; Neiman and Russell, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sinusoidal electrical stimulation to glass catfish shortens the interspike interval (ISI) in one half period and prolongs the ISI in the other half ( Bretschneider et al, 1985 ). Bursting patterns are considered to contribute to reliable signal transmission ( Izhikevich et al, 2003 ) and are often found in electroreceptors and their associated cells ( Wilkens et al, 1997 ; Neiman and Russell, 2002 ; Oswald et al, 2004 ; Lankheet et al, 2012 ). Daphnia or Ornstein-Uhlenbeck Gaussian noise induce bursting in the electroreceptors of paddle fish ( Wilkens et al, 1997 ; Neiman and Russell, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…For nearly half a century, spike-triggered averaging (STA) has been used in experimental neuroscience to gain insight into neuronal responses to stimulus features [1]–[6]. STA using broadband stochastic stimulation has revealed mechanisms that govern how inherently noisy sensory information might be encoded by neurons.…”
Section: Introductionmentioning
confidence: 99%